Fungicidas protetores no manejo da ferrugem da soja, processos fisiológicos e produtividade da cultura - Alves, Viviane Moreira (2016)
Currently, the management recommendations for asian soybean rust (ASR) has been based on the application of protective fungicides mixed with triazoles and stronilurins. Thus, this study aimed at assessing whether the increased productivity provided by the application of protective fungicides is due solely to the fungicidal action of the product or some physiological changes in the plant and which the latter would be. The experiment was conducted from March to July 2015 at the experimental station of Udi Research and Development in Uberlândia-MG, with the cultivar 97Y07 RR. The experimental design chosen for this study was comprised of a randomized block with four replications and 16 treatments: check, fluxapyroxad + pyraclostrobin (116.55 + 58.45 g ha-1), azoxystrobin + benzovindiflupir (90 + 45 g ha-1), trifloxystrobin + prothioconazole (60 + 70 g ha-1), tebuconazole + picoxystrobin (100 + 60 g ha-1), picoxystrobin + cyproconazole (60 + 24 g ha-1), mancozeb (1125 g ha-1), azoxistrobina + tebuconazole + difenoconazole (60 + 75 + 120 g ha-1), azoxystrobin + tebuconazole + difenoconazole + chlorothalonil ( 60 + 120 + 75 + 1440 g ha-1), and mistures fluxapyroxad + pyraclostrobin + mancozeb, azoxystrobin + benzovindiflupir + mancozeb, trifloxystrobin + prothioconazole + mancozeb, tebuconazole + picoxystrobin + mancozeb, picoxystrobin + cyproconazole + mancozeb, azoxystrobin + tebuconazole + difenoconazole + mancozeb, and azoxystrobin + benzovindiflupir + chlorothalonil, from the aforesaid doses. The first application of the treatments occurred in R1, in the absence of symptoms. The number of applications, intervals and the use of adjuvants were performed according to the recommendations by manufacturers. The variables analyzed were: disease severity, concentration of chlorophylls and carotenoids, photosynthetic rate (A), transpiration rate (E), stomatal conductance (gs), internal carbon concentration (Ci), instantaneous efficiency in water use (A/E), intrinsic water use efficiency (A/gs), and carboxylation efficiency (A/C). With these data collected, this study set to date the progress curve of each variable (AUPC). At the end of the crop cycle, the average of pods per plant was quantified, grain per pod, productivity and weight of 1,000 grains. It was concluded that: the addition of mancozeb to fluxapyroxad + pyraclostrobin, azoxystrobin + benzovindiflupir, trifloxystrobin + prothioconazole and tebuconazole + picoxystrobin potentiated the ASR control; adding mancozebe to the mixture azoxystrobin + benzovindiflupir provided better control of the disease compared to the addition of chlorothalonil; mancozeb amounts to AUPC concentration of photosynthetic pigments and when added to axozystrobin + tebuconazole + difenoconazole, increases the AUPC for total chlorophyll concentration, as well as when chlorothalonil was added; mancozeb added to the mix fluxapyroxad + pyraclostrobin raised the AUPC for A/Ci and A/gs, increasing the W1,000G and crop productivity; the addition of protectors similarly reflected on the productivity of culture.